(untitled) (Zbornik Pravnog fakulteta Sveučilišta u Rijeci, 2022)
The European Union macro-regional strategies represent a policy framework that aims to enable EU Member States and third countries sharing common interests to better coordinate their potentials in order to make the best possible use of available opportunities. This paper looks into the specificities of four EU macro-regional strategies covering 19 European Union Member States and nine non-EU countries. Given the challenging situation caused by the COVID-19 pandemic, it also considers the future perspectives of EU macro-regional strategies as well as their adaptability to new circumstances. More specifically, it focuses on intergovernmental initiatives and their implementation, underlying the importance of the application of the principle of subsidiarity. In addition, the aim of the paper is to provide a critical overview of the subject by highlighting two pivotal elements. First, it assesses whether the EU macro-regional strategies could be genuinely successful, given the fact that they do not have their separate allocation but use the existing funding instead. Second, it explores the ability of the EU macro-regional strategies to bridge wider EU-level policies on the one hand and local policies on the other. Finally, the idea of the paper is to offer an overview of the state of affairs when macro-regions are concerned.